Doing Business 2014 Regional Profile : East Asia Pacific Islands - World Bank; International Finance Corporation (Washington, DC, 2014)
Doing Business sheds light on how easy or difficult it is for a local entrepreneur to open and run a small to medium-size business when complying with relevant regulations. It measures and tracks changes in regulations affecting 11 areas in the life cycle of a business: starting a business, dealing with construction permits, getting electricity, registering property, getting credit, protecting investors, paying taxes, trading across borders, enforcing contracts, resolving insolvency and employing workers. This regional profile presents the Doing Business indicators for economies in East Asia Pacific Islands. It also shows the regional average, the best performance globally for each indicator and data for the following comparator regions: Common Market for Eastern and Southern Africa (COMESA), Caribbean States, East Asia and the Pacific (EAP), South Asia (SA) and OECD High Income.